An Insight into Foreign Language Learning Styles - Medved Krajnović, Marta (Array, 2008)
As a result of a more learner-centered approach in the field of foreign language teaching, the study of learning styles has received a lot of attention in the last two-three decades. The paper presents a brief overview of the current theoretical issues related to learning styles, and discusses the implications that a presence of learners with different learning styles might have on the teaching process. The paper also presents results of a research into the preferred ways of learning by a group of Croatian learners of English as a foreign language. Learning styles dichotomies that were investigated in this research were the following: field dependent/field independent, active/reflective, sensory/intuitive and visual/verbal.